A path appears : transforming lives, creating opportunity - Kristof, Nicholas D., 1959- (Alfred A. Knopf, 2014)
"From the authors of the Half the Sky, a unique and essential narrative about making a difference in the world--a roadmap to becoming a conscientious global citizen. Equal in urgency and compassion to Half the Sky, this galvanizing new book from the acclaimed husband and wife team is even more ambitious in scale: nothing less than a deep examination of people who are making the world a better place, and the myriad ways we can support them, whether with a donation of five dollars or five million, an inkling to help or a useful skill to deploy. With scrupulous research and on-the-ground reporting, the authors assay the art and science of giving--determining the current most successful local and global aid initiatives (on issues from education to inner-city violence to disease prevention), evaluating the efficiency and impact of specific approaches and charities, as well as fundraising. Most compellingly, perhaps, they show us how particular people have made a difference, and offer practical advice on how best each of us can give and what we can personally derive from doing so"--